Response of Pearl millet [Pennisetum glaucum (L.) R. Br. emend Stuntz] to Potassium Fertilization and Stress Mitigating Chemicals - Maya Meena; Manju Choudhary; Mahipal Singh Choudhary; B. L. Dudwal; Sanju Choudhary; Kamal Garg; Akshay Kumar Tiwari (Annals of Agricultural Research, 2022)
A field experiment entitled “Response of Pearl millet [Pennisetum glaucum (L.) R. Br. emend Stuntz] to potassium fertilization and stress mitigating chemicals” was conducted at Agronomy farm, S.K.N. College of Agriculture, Jobner (Rajasthan) during kharif, 2019 on loamy sand soil. The sixteen treatment combinations consisting of 4 treatments each of potassium levels (control, 10, 20 and 30 kg/ha) and stress mitigating chemicals (Control, thiourea, thioglycolic acid and thiosalicylic acid) were tested in randomized block design with three replications. Results indicated that progressive increase in level of potassium up to 20 kg/ha significantly improved the growth and yield determining characters of pearl millet viz., crop growth rate, effective tillers per plant, grain yield, stover yield over preceding levels. Further enhancement in potassium level to 30 kg/ha could not increase the above parameters significantly. However, plant height was recorded significantly higher due to potassium levels over control only. Results further showed that plant height, CGR, effective tillers/plant, grain and stover yields were significantly enhanced by foliar application of stress mitigating chemicals. By and large, application of thiourea being at par with TGA proved significantly superior over rest of the treatments in respect of the above parameters wherein all the chemicals being at par proved superior to control.